Content Analysis on Energy Issue in Kompas Daily - Luqman, Yanuar (Komunikator, 2019)
Energy sector has a very strategic role in Indonesia’s government besides infrastructure, food, education, health, and social protection. Energy issues are related with political, economic, social and cultural aspects. The government, in its national energy policy, manages the energy based on the principles of justice, sustainability, and environmental perception in order to create national energy independence and security. In the effort to create national energy independence and security, the government needs the participation of community and media. Media has a role in establishing public agenda to support government’s policy in energy sector. The role of mass media, in this case, is building public awareness about the importance of energy sector because it is not only for short-term benefit, but also for sustainable development.This research described how the media deliver the information about energy issues in Indonesia. The basic theory used in this research is the agenda setting theory and is complemented by other supporting theories. By using, quantitative descriptive content analysis research type, the issues on energy are seen with: technical, rubrication, writing style, writing technique and interviewee selection indicators. Kompas daily newspaper was the study subject in this research because it is a relatively consistent in editorial policy. The sample used was January - May 2018 edition. The results showed that Kompas Daily had not played much role in energy problems from various aspects.